The influence of ZnO/SiO2 nanocomposite concentration on rheology, interfacial tension, and wettability for enhanced oil recovery - Hassan, Y.M. (Institution of Chemical Engineers, 2022)
Oil reservoirs around the world are facing issues with the extraction ability of the accessible natural resources in the oil fields. Recent investigations on oil recovery have revealed that nanoparticles (NPs) possess a great potential on some parameters like rheology, interfacial tension (IFT), and rock wettability which help in uplifting the trapped oil. In this study, the influence of ZnO/SiO2 NPs concentration on oil recovery parameters (rheology, IFT, and wettability) has been investigated. The ZnO/SiO2 nanocomposite was synthesized and characterized using state-of-the-art techniques, afterwards, NPs were dissolved in brine followed by the formation of nanofluids at various concentrations. The results have indicated that the ZnO/SiO2 NPs at high concentration (0.1 wt. ) produced a considerable change in the rheology, IFT, and wettability. The viscosity (cP) of ZnO/SiO2 composite fluids has increased from 0.95 ± 0.03 to 1.29 ± 0.14, while the IFT (mN/m) was reduced from 12.93 ± 1.55 to 1.02 ± 0.05, and the contact angle (°) from 141 ± 28 to 62 ± 11. Overall, the changes in the rheology, IFT, and wettability were found to improve with an increase in ZnO/SiO2 NPs concentrations. © 2022 Institution of Chemical Engineers